Forgotten frontier - Tyson, Geoffrey, 1898- (Guwahati : Spectrum Publications : Sole distributors, United Publishers, 1945)
Role of Indian Tea Association in assisting the refugees from upper Burma escape into India during World War, 1939-1945.
Originally published: Calcutta : W.H. Targett & Co., 1945.
Keywords: Indian Tea Association; World War, 1939-1945 -- Burma; World War, 1939-1945 -- Refugees; Burma -- History -- Japanese occupation, 1942-1945.